Litter decomposition and faunal activity in Mediterranean forest soils: effects of N content and the moss layer - Garcia-Pausas, Jordi; Casals, Pere; Romanyà, Joan (Soil Biology and Biochemistry, 2004)
Accumulation of soil carbon is mainly controlled by the balance between litter production and litter decomposition. Usually In Mediterranean forests there are contrasting conditions in the distribution of faunal activity and the moss layer that may have different effects on litter decomposition. Decomposition and faunal activity were studied by exposing litter of contrasting quality (Pinus halepensis Mill. and Quercus ilex L.) for 3.5 yr in three Mediterranean pine forests of the eastern Iberian Peninsula. The effects of mosses on decomposition and on faunal activity were studied by exposing P. halepensis litter either on moss patches or directly on the forest ﬂoor. Faecal pellet production was used as an indication of faunal activity. Water availability or soil characteristics seem to limit faunal activities in the drier sites. Faecal pellets were not found during the ﬁrst stages of decomposition and in all sites they appeared when about a 30% of the initial litter had decomposed. Under wet conditions faecal pellet production was very high and a mass balance suggested that soil faunal activity may result in a net ﬂow of organic matter from the lower organic horizons to the surface Oi horizon. Mosses slightly increased mass loss of pine litter probably as a consequence of high potentially mineralizable nitrogen in the Oa horizon of moss patches and also, perhaps, as a consequence of the higher moisture content measured in the Oi horizon needles sampled among the mosses. In contrast, moss patches reduced faunal activity. The effect of litter quality on mass loss was not always signiﬁcant, suggesting an interaction between litter quality and site conditions. During the ﬁrst stages of decomposition there was N immobilisation in P. halepensis litter (poorer in N) and N release from Q. ilex litter (richer in N). In conclusion, in these forests soil microclimate and/or N availability appear to be more important controlling litter decomposition than the distribution of faunal activity.
Keywords: faecal pellets; litter decomposition; litter n content; Mediterranean forests; moss layer; nitrogen dynamics